Estudio de factibilidad para la creación de una cooperativa de ahorro y crédito en asociación con los microempresarios y organizaciones comunitarias de la parroquia de La Merced, Valle de los Chillos, provincia de Pichincha - Fuentes Coyasamín, Marisela Fernanda (2013)
The limited financial capacity prevents many access credit in the banking system especially those starting their projects, generating the need for alternatives to encourage saving and financing, a valid alternative that requires attention is the union system and credit, characterized by solidarity, mutual aid, gender equity, self-management, social responsibility, respect for identity and democratic control fundamental basis for the development of its exercises, find a solution popular development and microenterprise sectors of the country. This project seeks to promote savings and credit policy, provide micro-entrepreneurs, community and the parish of La Merced, financial support for their projects and businesses, for this is a clear need and acceptance of the creation of a cooperative parish, associated with organizations.